ISSUES OF DIFFERENTIAL DIAGNOSIS OF INFLAMMATORY AND FUNCTIONAL INTESTINAL DISEASES (LITERATURE REVIEW) (World Bulletin of Public Health, 2023)
To summarize the main literature data and our own accumulated practical experience in everyday pathological and anatomical diagnosis of inflammatory bowel disease (IBD) for better presentation of morphological features and histological findings. The microscopic picture of IBD is often represented by a combination of basic histologic features that may be found in other diseases and only rarely can be considered pathognomonic. No single histologic feature can be used in isolation to make a diagnosis of ulcerative colitis or Crohn's disease. Diagnostic accuracy increases if several signs are taken into account at once, if changes within one or several parts of the intestine are analyzed, and if the identified changes are compared with the clinical picture of the disease.